Defending a single object against an attacker trying to detect a subset of false targets. (May 2016) - Peng, R.; Zhai, Q.Q.; Levitin, G.
Abstract: Deployment of false targets can be a very important and effective measure for enhancing the survivability of an object subjected to intentional attacks. Existing papers have assumed that false targets are either perfect or can be detected with a constant probability. In practice, the attacker may allocate part of its budget into intelligence actions trying to detect a subset of false targets. Analogously, the defender can allocate part of its budget into disinformation actions to prevent the false targets from being detected. In this paper, the detection probability of each false target is assumed to be a function of the intelligence and disinformation efforts allocated on the false target. The optimal resource distribution between target identification/disinformation and attack/protection efforts is studied as solutions of a non-cooperative two period min–max game between the two competitors for the case of constrained defense and attack resources. Highlights: A defense-attack problem is studied as a two-period min–max game. Both intelligence contest over false targets and impact contest are considered. Optimal defense and attack strategies are investigated with different parameters.